Early and vigorous fluid resuscitation prevents acute renal failure in the crush victims of catastrophic earthquakes - Gunal, AI; Celiker, H; Dogukan, A; Ozalp, G; Kirciman, E; Simsekli, H; Sever, MS (Amer Soc Nephrology, 2004)
This study analyzes the effects of fluid resuscitation in the crush victims of the Bingol earthquake, which occurred in May 2003 in southeastern Turkey. Questionnaires asking about demographic, clinical, laboratory, and therapeutic features of 16 crush victims were filled in retrospectively. Mean duration under the rubble was 10.3 +/- 7 h, and all patients had severe rhabdomyolysis. Fourteen patients were receiving isotonic saline at admission, which was followed by mannitol-alkaline fluid resuscitation. All but two patients were polyuric. Admission serum creatinine level was lower than and higher than 1.5 mg/dl in 11 and 5 patients, respectively. Marked elevations were noted in muscle enzymes in all patients. During the clinical course, hypokalemia was observed in nine patients, all of whom needed energetic potassium chloride replacement. Four (25%) of 16 victims required hemodialysis. Duration between rescue and initiation of fluids was significantly longer in the dialyzed victims as compared with non-dialyzed ones (9.3 +/- 1.7 versus 3.7 +/- 3.3 h, P < 0.03). Sixteen fasciotomies were performed in 11 patients (68%), nine of which were complicated by wound infections. All patients survived and were discharged from the hospital with good renal function. Early and vigorous fluid resuscitation followed by mannitol-alkaline diuresis prevents acute renal failure in crush victims, resulting in a more favorable outcome.
Keywords: Hanshin-Awaji-Earthquake; Marmara Earthquake; Traumatic Rhabdomyolysis; Management; Disaster